Non-vitamin K oral anticoagulants at the time of cardiac rhythm device surgery: A systematic review and meta-analysis. Issue 188 (April 2020) - Creta, Antonio; Finlay, Malcolm; Hunter, Ross J.; Chow, Anthony; Sporton, Simon; Muthumala, Amal; Dhillon, Gurpreet; Papageorgiou, Nikolaos; Waddingham, Peter; Ahsan, Syed; Dhinoja, Mehul; Earley, Mark J.; et al.
Abstract: Introduction: Use of non-vitamin K oral anticoagulants (NOACs) has rapidly increased worldwide. We aimed to systematically assess the available evidence regarding the safety and efficacy of NOACs in patients undergoing cardiac implantable electronic device (CIED) surgery. Methods: We performed a systematic literature search. Eligible randomised controlled trials and cohort studies were included. The primary outcome measures were clinically significant device-pocket haematoma and thromboembolic events. Results: A total of 12 studies were included, equating to 2120 patients. The separate pooling of rate of events showed a low incidence of clinically significant device-pocket haematoma, although numerically higher in patients on continued (1.5%; CI95% 0.8–3.0) versus interrupted NOAC (0.9%; CI95% 0.5–1.7). The rate of any device-pocket haematoma was numerically higher in the continued versus interrupted NOAC group (5.4%; CI95% 3.8–7.7 versus 2.4%; CI95% 1.8–3.3). The incidence of thromboembolic events (0.4%; CI95% 0.2–0.8) was low and comparable. From a meta-analysis of 3 studies (equating to 773 subjects) allowing for a comparison of continued versus interrupted NOAC, we found no significant difference between the 2 strategies in terms of clinically significant pocket haematoma (RR1.14; CI95% 0.43–3.06, p = 0.79), thromboembolic complications (RR1.03; CI95% 0.06–16.37, p = 0.98), and any pocket haematoma (RR1.19; CI95% 0.65–2.20, p = 0.57). Conclusion: Use of NOACs at the time of CIEDs surgery appears to be safe, and either strategy of peri-procedure continuation or interruption might be reasonable. However, continuation of NOAC seems to be associated with a numerically higher rate of bleeding complications. Certainty of the evidence is low, and further studies are required to confirm these findings. Highlights: Non-vitamin K oral anticoagulants (NOAC) during pacemaker or defibrillator surgery are safe. Either NOAC continuation or interruption appears reasonable for atrial fibrillation. Incidence of bleeding and thromboembolism is low. Incidence of pocket haematoma appears numerically higher with NOAC continuation.